THE INDIVIDUATION OF HERO IN KHALED HOSSEINI’S THE KITE RUNNER - Afriani Ulya; Muarifuddin . (ETNOREFLIKA: Jurnal Sosial dan Budaya, 2015)
This study is aimed to analyze the process of Individuation of Hero in Khaled Hosseini’s novel “The Kite Runner” in the case of psychoanalitic. This phenomenon is showed by Amir’s psychology. The problem in this study formulated: How is The Individuation of Hero in Khaled Hosseini’s The Kite Runner?”. The source of data in this study is The Kite Runner novel which published on 2003 in America. The data collected through annotating, previewing, and interpreting to get a complete analysis about The Individuation of Hero in Khaled Hosseini’s The Kite Runner. Carl Gustav Jung’s Psychoanalitic is used as a tool of analysis to support the finding on The Individuation of Hero in Khaled Hosseini’s The Kite Runner. The result of analysis found that the Individuation of Hero namely Amir as major character in Khaled Hosseini’s The Kite Runner is able to achieve the individuation process with the existence of Persona, Anima, Shadow, and Self in his personality. Then, the major character is able to transform them into the conscious mind and at the same time synchronize and harmonize them, meaning that the major character is able to minimize the persona, realize his anima, balance his shadow, enhance his self gradually leading to the highest hierarchy in the center of the psyche. The individuation process of the major character occurs when he has to face his grim reality and force him to return to Kabul to save Sohrab (Hassan’s son) who goes through the sexual attack. Hassan’s loyalty to get the blue kite proves that he has led a life of virtue. Having realized that he has been a true coward, Amir feels sure that he can repay a kindness given by Hassan by means of returning to Kabul to save Sohrab (Hassan’s son). Amir tries so hard to overcome all the obstacles for the sake of saving Sohrab. When Amir manages to see Sohrab, his disguising is recognized. It turns out that Assef, being the stooge of Taliban’s leader, is the mastermind behind the locking up. Assef used to intimidate Amir and he is also a Pashtunese. Amir begs for mercy that Sohrab is allowed to set free, but he rejects it. Amir makes use of the moment to repay a kindness given by Hassan. Finally, Amir manages to set Sohrab free and takes him to the US and adopts him as his own son. Keywords: individuation, hero, persona, anima, shadow, self.